A new lithospheric model in the eastern part of the Western Carpatians: 2D integrated modelling - Petra HLAVŇOVÁ; Miroslav BIELIK; Jana DÉREROVÁ; Igor KOHÚT; Mariana PAŠIAKOVÁ (Contributions to Geophysics and Geodesy, 2015)
Using 2D integrated geophysical modelling we recalculated lithospheric model along transect KP-X in the eastern part of theWestern Carpathians. Our model takes into account the joint interpretation of the heat flow, free air anomalies, topography and geoid data. A more accurate model of lithospheric structure has been created, especially the lithosphere-astenosphere boundary. Lithosphere thickness in the study region increases from the area of the Pannonian Basin where we modelled it at the depth of 80 km towards the oldest and coolest area of the European Platform where it reaches about 150 km. In the Pannonian Basin the modelled Moho depths reach about of 25 km and it decreases towards theWestern Carpathians. TheWestern Carpathian’s crustal thickness varies from about 30 km to 45 km. The largest crustal thickness (45 km) has been located beneath the Externides (Carpathian Foredeep) of the Western Carpathians. In the direction of the European platform a Moho depth gradually increases until the end of the profile, where the crustal thickness reaches of about 42 km. Our modelling has confirmed the existence of an anomalous body with average density of 2850 kgm-3 seated mostly in the lower crust. Its uppermost boundary reaches a depth of about 12 km. The lower crust beneath the Western Carpathian Externides is much thicker (20 km) in comparison beneath the Pannonian Basin, where it is only 8 km on average.